MbMYBC1, a M. baccata MYB transcription factor, contribute to cold and drought stress tolerance in transgenic Arabidopsis - Liu, Wanda; Wang, Tianhe; Wang, Yu; Liang, Xiaoqi; Han, Jilong; Han, Deguo (Frontiers in Plant Science, 2023)
Cold and drought stress considerably suppress the development of plants. In this study, a new MYB (v-myb avian myeloblastosis viral)TF gene, MbMYBC1, was isolated from the M. baccata and located in nucleus. MbMYBC1 has a positive response to low temperature and drought stress. After being introduced into Arabidopsis thaliana, the physiological indicators of transgenic Arabidopsis had corresponding changes under these two stresses, the activities of catalase (CAT), peroxidase (POD) and superoxide dismutase (SOD) increased, electrolyte leakage rate (EL) and the content of proline increased, but the content of chlorophyll decreased. In addition, its overexpression can also activate the downstream expression of AtDREB1A, AtCOR15a, AtERD10B and AtCOR47 related to cold stress and AtSnRK2.4, AtRD29A, AtSOD1and AtP5CS1 related to drought stress. Based on these results, we speculate that MbMYBC1 can respond to cold and hydropenia signals, and can be used in transgenic technology to improve plant tolerance to low temperature and drought stress.